If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64 + 5y + -25 = 16y + -10 + -4y Reorder the terms: 64 + -25 + 5y = 16y + -10 + -4y Combine like terms: 64 + -25 = 39 39 + 5y = 16y + -10 + -4y Reorder the terms: 39 + 5y = -10 + 16y + -4y Combine like terms: 16y + -4y = 12y 39 + 5y = -10 + 12y Solving 39 + 5y = -10 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 39 + 5y + -12y = -10 + 12y + -12y Combine like terms: 5y + -12y = -7y 39 + -7y = -10 + 12y + -12y Combine like terms: 12y + -12y = 0 39 + -7y = -10 + 0 39 + -7y = -10 Add '-39' to each side of the equation. 39 + -39 + -7y = -10 + -39 Combine like terms: 39 + -39 = 0 0 + -7y = -10 + -39 -7y = -10 + -39 Combine like terms: -10 + -39 = -49 -7y = -49 Divide each side by '-7'. y = 7 Simplifying y = 7
| 1.2*(x+5)=1.6*2x+5 | | x^2-15x-3250=0 | | 3(2x-5)=0 | | 19-17=63 | | y^20/y^6 | | 5x+2y+7x+20=180 | | 14x-3y=24 | | -4(x+9)=-88 | | 2y^2+5y-15=0 | | x+7x=176 | | 10x-y=-3 | | A=1/12(360) | | 12y+3=9a-15 | | 3(x+2)-x=11 | | 5-1=1 | | (540-x^2)-(x^2+6x)=0 | | 15x-20=-300 | | 1+2n+5=18 | | =3(2r+7)+3(3r-5) | | 3.14/4x=3d | | 6d+18= | | 9+ln(8x)=21-2ln(x) | | 7-15=5x | | 30t^2=22t | | (6+x)(5x-6)= | | -7(5m)= | | 25t^2=25 | | 7.5*6.3=x | | -3x-8=46 | | p(x)=x^2-25 | | 3x+69=8x-6 | | 12(4X-3)=4(12X+5) |